(untitled) (ADMPG Journal, 2023)
This work aims to analyze the consumption of social networks by clients of a beauty salon located in the city of Cianorte/PR. Such an approach is necessary to understand how much people are connected in social networks, a fact that helps the company improve its relationship with customers. The research is characterized as quantitative and descriptive and was carried out through a questionnaire containing 10 multiple-choice questions, prepared in Google Forms and sent via WhatsApp. The questionnaire was sent to 40 clients of the salon who frequent the salon. 27 responses were obtained. The results showed that people are connected most of the time and that Instagram is the social network most accessed by the research participants. The information obtained serves as a basis for drawing up a publication plan for publicizing the company’s services.